Alternative procedure for determining lysine maintenance requirement in poultry - Dorigam, Juliano Cesar de Paula; Silva, Edney Pereira da [UNESP]; Sakomura, Nilva Kazue [UNESP]; Peruzzi, Nelson Jose [UNESP]; Lima, Michele Bernardino de [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
The objective with this study was to determine the lysine maintenance requirements (LMR) of male and female broilers as animal models. A total of 252 birds were used for nitrogen balance trials during three periods (I: 6-21, II: 22-37, and III: 38-53 days). Six lysine levels were used (2.76, 5.88, 8.99, 12.1, 15.2, and 18.3 g kg(-1)) with six replications. A control group also included, totalizing seven treatments for males and females for each assay. The experimental period was 15 days. The response variables included nitrogen intake (NI) and excretion (NEX), and their difference was assumed to be deposited as nitrogen. An exponential regression between NEX and lysine intake (LI) was fitted, and LMR was estimated when LI = 0. The daily values for LMR were 9.29, 33.4, and 40.2 mg BW0.67 kg(-1) for males and 9.36, 30.0, and 39.4 mg BW0.67 kg(-1) for females. The final value for both sexes were 10.1 (period I), 31.5 (period II), and 39.8 mg BW0.67 kg(-1) (period III). Expressed as body protein weight at maturity (BPm), the LMR were 172 and 148 (period I), 216 and 207 (period and 189 and 180 mg BPm0.73 kg(-1) (period III) for males and females, respectively. The results provided ranges of LMR values recommended in previous studies, validating this procedure. The procedure to estimate the requirements presented here provides new insights into the model of amino acid requirement estimations.
Keywords: amino acid; exponential model; likelihood ratio; maintenance; nitrogen balance